Detection of Neutralizing Antibodies to Tembusu Virus: Implications for Infection and Immunity - Lv, Junfeng; Yang, Lixin; Qu, Shenghua; Meng, Runze; Li, Qingxiangzi; Liu, Huicong; Wang, Xiaoyan; Zhang, Dabing (Frontiers in Veterinary Science, 2019)
Neutralizing antibodies are the key mediators of protective immune response to flaviviruses after both infection and vaccination. Plaque reduction neutralization test (PRNT) is considered the "gold standard" for measurement of the immunity. To date, little is known regarding neutralizing antibody response to Tembusu virus (TMUV), a novel flavivirus emerging in ducks in 2010. Here, we developed a PRNT for detection of TMUV neutralizing antibodies. Following optimization and validation, the PRNT was applied to test serum samples from different flocks of ducks. Using sera prepared in experimental conditions, the levels of 50% end point titer (neutralizing dose, ND50) generated from positive sera (5012 to 79433) were significantly higher than those from mock-infected sera (10 to 126), indicating that the test can be used in the detection of TMUV-specific neutralizing antibodies. Dosedependent efficacy test of a cell-derived 180th passage of a plaque-purified virus of the PS TMUV isolate (PS180) in combined with immunization-challenge experiments revealed that ND50 titer of approximately 1258 is the minimum capable of providing adequate protection against challenge with virulent TMUV. In the investigation of serum samples collected from three flocks infected by TMUV and four flocks vaccinated with a licensed attenuated vaccine (the 120th passage virus), ND50 titers peaked at 1 week after both disease onset (7943 to 125893) and vaccination (3612 to 79432), and high levels of ND50 titer were detected in sera collected at 15 weeks after disease onset (5012 to 63095) and 17 weeks after vaccination (3981 to 25119). Together these findings demonstrated that spontaneous and experimental infections by TMUV and vaccination with the licensed TMUV attenuated vaccine elicit high, long-lasting neutralizing antibodies. The highest ND50 titer of neutralizing antibodies elicited by PS180 was determined to be 3162, suggesting that attenuation of TMUV by more passages has a dramatic impact on the neutralizing antibody response of the virus.